DEVELOPMENT OF INSURANCE COMPANIES IN THE ECONOMIC CENTER OF THE COUNTRY - Nosirov Jasur (Scholar Express Journals, 2024)
The main focus of this article is on the insurance sector and economic development of countries in transition; while some of them have already become members of the European Union, others are still in the access to the EU procedure. From the data collected by using an empirical method, it can be observed that the development of the insurance market has had a positive influence on economic growth. The importance of the insurance sector can be observed in the results of the displayed types of insurance in the period from 2020 to 2024. The confirmation of market development is also located in the laid and paid claims, which provide policyholders with security and confidence in insurance companies.
Keywords: Insurance; development; economic growth